Sensitive and selective detection of cancer biomarkers with molecularly imprinted biosensors - Sibel Büyüktiryaki (Talanta Open)
Accurate and reliable detection of cancer biomarkers plays a pivotal role in early diagnosis, disease progression monitoring, and effective treatment strategies. Molecularly imprinted polymers (MIPs), with their high selectivity and stability, have emerged as powerful tools for biomarker detection. This review explores the fundamental principles of MIPs and their tailored synthesis for biological markers. Special emphasis is placed on integrating MIPs with analytical techniques such as optical and electrochemical sensing platforms. Moreover, it highlights their success in real biological matrices and addresses the challenges and opportunities for developing advanced solutions. Finally, the review addresses challenges and future directions, emphasizing the critical role of MIP technology in achieving ultra-sensitive, cost-effective, and portable diagnostic solutions. This review aims to highlight the potential of MIP-based sensors for the selective and sensitive detection of cancer biomarkers and to serve as a guide for researchers in the field.